Ultrasonic transducers using radial vibrations of a piezoelectric disk - GOLANOWSKI, Jerzy; GUDRA, Tadeusz (Archives of Acoustics, 1979)
Suggestions concerning the use of radial vibrations of a piezoelectric disk in ultrasonic transducers working in the frequency range below 100 kHz are presented. Experimental data from investigations of two types of transducers are given, one using axial coupling of a piezoelectric disk with a metal rod vibrating in the longitudinal mode, the other using circumferential coupling of a piezoelectric disk and a metal plate. The amplitude and phase characteristics of admittance, the resonance curves, the temperature characteristics of impedance and the resonance displacement amplitudes are presented.